Diagnosing the effects of leader-member exchange quality on performance in the context of organizational culture: a case from Turkish family-owned businesses - Ayyildiz Unnu, Nazli Ayse; Kesken, Julide (Journal of Business Economics and Management, 2014)
The main purpose of this study was to diagnose the effects of leader-member exchange (LMX) quality on performance in the context of organizational and Turkish culture. The study was conducted in two family-owned businesses (FOBs), as they are very important structures in which in-group and out-group formations can be seen. Firm A (33 employees representing 41 dyads) and Firm B (61 employees representing 60 dyads) were especially chosen as they enabled us to apply the coding system leading to effective evaluation of surveys as the unit of analysis is “dyads”. In this framework, this study offers an important contribution to the international management literature as positive effects of LMX quality on firm performance, subordinate performance, intention to leave and job satisfaction were found within the context of organizational and Turkish culture. As the proportion of FOBs is almost 95% in Turkey, they represent Turkish economy and business culture well, leading to more generalizable results. Thus, firms can lead to increase in both subordinate and firm performance by creating an organizational culture in which high quality leader-member relationships are emphasized, finally leading to positive organizational outcomes.